Profile of Learning Outcomes and Student Activity in Learning Natural Sciences at SMPN 2 Karangawen - Ivonne Susana Berlin; Ary Susatyo Nugroho; Siti Patonah; Muhammad Syaipul Hayat (Jurnal Penelitian Pendidikan IPA, 2025)
This article as a literature review aims to understand the characteristics of learning achievement and the level of student participation in the Natural Sciences learning process. At SMPN 2 Karangawen. The fact that in the field many students experience difficulties when learning and are not active when there is material they don't understand, this is what prompted researchers to find out the learning outcomes and student activity in science learning at SMPN 2 Karangawen. This research uses descriptive qualitative methods and the subjects of this research involve 31 students in class IX of SMPN 2 Karangawen. Sample selection in this research was carried out using a simple random sampling method. Information collection was carried out using the activity questionnaire method and recording learning outcomes. In this research, descriptive statistical analysis techniques were used to analyze the data. The findings show: 1) Recording of science learning outcomes through the classroom observation method is quite 42%. 2) The profile of student activity in science learning can be categorized as less active because only 2 instruments are included in the good category, namely seen from the results of visual activities 53% and writing activities 71%. At the same time, there are 3 indicators that fall into the category, namely oral activities 63%, listening activities 65%, and activity metrics 57%.